Analysis of surgical reserves of packed red blood cells in an oncology hospital (Research, Society and Development, 2022)
Blood plays a key role in maintaining patient survival during elective surgical procedures. The transfusion of packed red blood cells is able to quickly correct the anemic state and improve oxygenation, however, its performance is associated with adverse outcomes. In cancer patients, it is linked to worse survival and higher risk of recurrence. Thus, we sought to analyze the reserves of packed red blood cells and evaluate the profile of patients undergoing elective surgeries in an oncology hospital. It was an observational, descriptive study with a cross-sectional design, with analysis of all forms of requests for packed red blood cells s for surgical reserve, with a sample of 1386 requests. Women and the age group between 40 and 79 years were the public most transfused with packed red blood cells, the surgeries were large, the sectors responsible for the largest number of transfusions were oncoabdominal surgery and oncogynecology, as well as the pathologies of these sectors cancer of the stomach and cervical cancer; procedures with excess compatibility were surgical treatment for epilepsy, trachelectomy, arteriography and splenectomy; most procedures had a rate of transfused patients > 10% for whom it is necessary to reserve the blood component. In the analysis of the Maximal Blood Order Schedule, it was noted that a wide range of procedures requires two units of packed red blood cells. This generated subsidies to encourage the rational use of blood in the health institution.